2021
DOI: 10.1039/d0fo03326j
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and structure–activity relationship of novel umami peptides isolated from Thai fish sauce

Abstract: Fish sauce has a prominent umami flavor. In this study, umami peptides were isolated, purified and identified from Thai fish sauce, and their structure-activity relationship were analyzed. Six novel umami...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…As the availability of proteins in high‐throughput‐sequencing projects increases, the number of potential umami peptides is expected to grow rapidly. For the discovery of umami peptides from the identified peptides, the traditional method is to screen by structure–activity relationship or the frequency of the biologically active fragments (Bu et al., 2021), but it is difficult to apply high‐throughput sequencing. Molecular docking and machine learning are considered to be a high‐throughput and rapid form of technology that can be applied to initially screen umami peptides from the identified peptide library.…”
Section: Screening Of Umami Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…As the availability of proteins in high‐throughput‐sequencing projects increases, the number of potential umami peptides is expected to grow rapidly. For the discovery of umami peptides from the identified peptides, the traditional method is to screen by structure–activity relationship or the frequency of the biologically active fragments (Bu et al., 2021), but it is difficult to apply high‐throughput sequencing. Molecular docking and machine learning are considered to be a high‐throughput and rapid form of technology that can be applied to initially screen umami peptides from the identified peptide library.…”
Section: Screening Of Umami Peptidesmentioning
confidence: 99%
“…Umami substances stay in the mouth for a long time, however, and it is difficult to accurately measure the senses and evaluate the intensity of the umami taste (Chung et al, 2015). The umami taste intensity usually is evaluated by an intensity scale (Bu et al, 2021), taste dilution analysis , or two-alternative forced choice (2-AFC) method . Chung et al (2015) compared the 2-AFC, ranking method, and scoring method to distinguish the taste intensity of an MSG solution and showed that 2-AFC was the most effective method to identify different umami taste samples, but it could not produce intensity values.…”
Section: Evaluation Of Umami Intensity By Sensory Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between peptide and receptor affects the subsequent intracellular taste perception signal transduction and brain response ( 28 ). It was found that T1R1-VFT was a potential binding site ( 9 , 10 , 25 ) for taste peptides; At the same time, some studies revealed that the taste peptides were mainly bound to T1R3-VFT ( 7 , 8 , 20 , 23 , 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking technology simulates the biological process of molecular interaction, reveals the structural basis of ligand recognition by receptor and its binding with the receptor in receptor-ligand interaction, and predicts the taste perception mechanism of taste peptides at the atomic level. Molecular docking technology has been applied to the binding sites and interaction mechanisms between taste peptides and their taste receptors T1R1/T1R3 ( 7 10 ). The molecular docking technique was used to explore the active structure and taste perception mechanism of the taste peptide of S. rugosoannulata , combined with the taste receptors T1R1/T1R3, which could provide theoretical support for understanding its pleasant taste.…”
Section: Introductionmentioning
confidence: 99%